Increasing chemisorbed silane coupling agents in surface‐treated layer of silica particles. Issue 44 (21st June 2021) - Nakamura, Takashi; Tsutsumi, Ryota; Hashiguchi, Chisato; Terao, Toshiki; Manabe, Kei; Hirai, Tomoyasu; Fujii, Syuji; Nakamura, Yoshinobu
Abstract: In the surface treated inorganic particles with silane coupling agent (SCA), chemisorbed and physisorbed molecules are present in the treated layer. Increasing the amount of chemisorption by increasing the molecular weight of SCAs was investigated. Oligomers formed via self‐condensation during storage more than 10 days at room temperature for 3‐methacryloxypropyltrimethoxysilane‐treated silica particles. Monomeric SCA evaporates easily by heating. The oligomers restrict evaporation, and heating increases the chemisorption. The influence of molecular weight of SCA was investigated. In the case of amino group, the amount of chemisorbed was greater for aminoethylaminooctyltrimethoxysilane with high molecular weight than for 3‐aminopropyltriethoxysilane. For SCAs with hydrocarbon chains, the amount of chemisorption was lower for both low molecular weight molecules and decyltrimethoxysilane (D) with a high molecular weight. For fluorocarbon chains, the amount of chemisorption was lower for low molecular weight molecules, whereas it increased significantly by heating for high molecular weight type of 1 H, 1 H, 2 H, 2 H ‐heptadecafluorodecyltriethoxysilane (F). Wide‐angle X‐ray diffraction analysis of F‐treated silica particles showed that the fluorocarbon chains formed an ordered structure. There was no such indication for the D‐treated system. This ordered structure seems to influence on higher chemisorption for F‐treated systems. Abstract : AFM image of mica surface treated with amino functional silane coupling agent with long chain.